(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Angular introduced Standalone Components, marking a significant evolution in the framework’s architecture. This feature simplifies module dependency management by allowing components, directives, and pipes to function independently of Angular Modules (NgModules). This paper explores the implications of Standalone Components on Angular development, including reduced boilerplate code, improved performance, and enhanced scalability. By examining the motivations, implementation strategies, and benefits, we aim to understand how this shift promotes a more modular and lightweight design in Angular applications.